2022
DOI: 10.3390/su141912293
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Green Building Development in China: Advantages, Challenges and Future Directions

Abstract: In the 21st century, traditional construction activities exert a severe negative influence on the environment and ecology. To mitigate the negative influence of construction, green buildings have received increasing attention worldwide. Compared with conventional buildings, green buildings have significant advantages for environmental conservation and public health. Although green buildings bring excellent benefits, the development status of green buildings in China is still unsatisfactory. To enhance the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 233 publications
1
5
0
Order By: Relevance
“…In addition, the paper emphasises the importance of using local and natural materials in sustainable building. This is in line with previous research that has analysed the ecological aspects of building, such as Cao et al who analysed the use of natural materials in building as a way to reduce environmental impact [92].…”
Section: Lca Simulationssupporting
confidence: 91%
“…In addition, the paper emphasises the importance of using local and natural materials in sustainable building. This is in line with previous research that has analysed the ecological aspects of building, such as Cao et al who analysed the use of natural materials in building as a way to reduce environmental impact [92].…”
Section: Lca Simulationssupporting
confidence: 91%
“…Overall, the research [13] suggests that green building knowledge can play an important role in increasing the implementation of IoT technologies in real estate development. Developers who are knowledgeable about green building practices are more likely to understand the benefits of IoT technologies and how to effectively integrate these technologies into their buildings [14].…”
Section: Introductionmentioning
confidence: 93%
“…Research has shown that developers with higher levels of green building knowledge are more likely to adopt IoT technologies in their buildings [11][12][13][14]. This is because green building knowledge helps developers identify the benefits of the IoT and understand how to effectively integrate these technologies into their buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key principles of green building include energy efficiency, resource efficiency, environmental conservation, and the health and well-being of occupants [13]. According to Cao et al, despite the late start, China's green building domain has developed rapidly recently [14].…”
Section: Green Building Practicesmentioning
confidence: 99%